Marketing channel strategy - Palmatier, Robert W.; Stern, Louis W., 1935-; Ansary, Adel I. (New York ; London : Routledge Taylor & Francis Group, 2016)
Marketing Channel Strategy: An Omni-Channel Approach is the first book on the market to offer a completely unique, updated approach to channel marketing. Palmatier and Sivadas have adapted this classic text for the modern marketing reality by building a model that shows students how to engage customers across multiple marketing channels simultaneously and seamlessly. The omni-channel is different from the multi-channel. It recognizes not only that customers access goods and services in multiple ways, but also that they are likely doing this at the same time; comparing prices on multiple websites, and seamlessly switching between mobile and desktop devices. With the strong theoretical foundation that users have come to expect, the book also offers lots of practical exercises and applications to help students understand how to design and implement omni-channel strategies in reality. Advanced undergraduate and graduate students in marketing channels, distribution channels, B2B marketing, and retailing classes will enjoy acquiring the most cutting-edge marketing skills from this book.
The omni-channel ecosystem -- Channel basics -- Channel power -- Channel relationships -- Channel conflict -- Retailing structures and strategies -- Wholesaling structures and strategies -- Franchising structures and strategies -- Channels and international markets -- End-user analysis: segmentation and targeting -- Omni-channel strategy.
Includes bibliographical references and index.
Keywords: Marketing channels; Marketing -- Management; Marketing channels; Marketing -- Management